Aplicación de las metodologías de observación directa e indirecta en el monitoreo del zorro andino (Lycalopex culpaeus), para determinar su presencia en los páramos de la parroquia de Mulaló - Zurita Moreno, Jhonny Andree (2022)
The objective of this research was to demonstrate the presence of the Andean fox in the parish of Mulaló Canton Latacunga Province of Cotopaxi in the period May 2022 - August 2022. Thus, by conducting transects in specific areas, it was possible to record the species directly (observation of the species) and indirectly (sighting of tracks and feces). This led to the confirmation of the existence of the moor fox in the parish of Mulaló, evidencing several threats that put the survival of the species at risk, as well as the presence of other species such as the hare, one of the main foods of the Andean fox, and the presence of feral dogs, which represent a threat to the natural habitat of the fox. Through the presence of these animals, it will be possible to determine the future population of the moor fox. Given this research, we recommend an in-depth study of the species in the sector and the problems that the different factors such as anthropogenic activities that we recorded in the data sheet, among which are livestock, agriculture, deforestation and a special introduced species such as feral dogs, pose to the specimen under investigation. Taking into account all the information gathered from this research, it is proposed to create public policies and raise awareness in society as well as implement sustainable tourism projects and use it as a tool for the conservation of these emblematic species and the benefit of the communities.